Change in Attachment Dimensions and Reflective Functioning Following Emotionally Focused Group Therapy for Binge Eating Disorder. Issue 3 (3rd July 2018) - Compare, Angelo; Maxwell, Hilary; Brugnera, Agostino; Zarbo, Cristina; Dalle Grave, Riccardo; Tasca, Giorgio A.
ABSTRACT: The current study examines change in attachment variables from pre- to six months post-emotionally focused group therapy (EFGT) for binge eating disorder (BED). A clinical sample of 118 women and men with BED attended 20 sessions of EFGT and completed the Adult Attachment Interview pre- and six months post-treatment. There was a significant increase in secure attachment style classification, significant increases in Coherence of Mind and Reflective Functioning scores, and significant decreases in both unresolved/disorganized attachment style classification and scale scores from pre- to six months post-treatment. Interventions specific to EFGT, common therapeutic factors and group process interventions may have contributed to changes in these attachment variables. The current study demonstrated that EFGT is a promising treatment for facilitating change in attachment in women and men with BED.